Management of myocardial infarction in a rural area - Black, Douglas P. (1973)
In an attempt to determine the most appropriate type of facility for the treatment of myocardial infarction in a rural community, the five-year experience of a practice serving 10,000 people is reviewed. This population is found to have a low incidence of myocardial infarction, a low death rate from the condition both in hospitalized patients and in the general population, and a low incidence of complications in the survivors. None of the deaths either in or out of hospital would likely have been prevented through the use of specialized facilities. It is concluded that no such facilities are necessary in this community and that other areas considering their acquisition should justify the need on the basis of their own experience and not on accounts in the literature.